건부항요법이 간호사의 견통과 피로도에 미치는 영향 - 손도리나; 윤현민; 정향미; Sohn, Dorina; Yoon, Hyun-Min; Jung, Hyang-Mi (Journal of pharmacopuncture, 2011)
Objective : This research was done to identify the effects of dry cupping therapy on the shoulder pain and fatigue of nurses. Methods : The research design was time series design. The participants were 27 nurses with shoulder pain at P University Hospital in Busan metropolitan city from July 6, 2009 to August 3, 2009. The dry cupping therapy was done 4 times, twice a week for 2 weeks. Before intervention, the severity and frequency of pain and fatigue were measured three times at one week intervals, and then those were measured after one week and two weeks of experimental treatment. The results were analyzed using descriptive statistics, paired t-test and repeated measure ANOVA with the SPSS program. Results : There were statistically significant difference in severity and frequency of shoulder pain, and fatigue after dry cupping therapy. Dry cupping therapy was effective for the management of shoulder pain and fatigue among nurses in this study. Conclusion : Therefore dry cupping therapy can be considered an effective nursing intervention that relieves shoulder pain and fatigue of nurses.